Global research trends in transcranial magnetic stimulation for stroke (1994–2023): promising, yet requiring further practice - Li, Xin-Yu; Hu, Rong; Lou, Tian-Xiao; Liu, Yang; Ding, Ling (Frontiers in Neurology, 2024)
Background: Scholars have been committed to investigating stroke rehabilitation strategies for years. Transcranial magnetic stimulation has been increasingly utilized in contemporary stroke rehabilitation research since its invention. Evidence has shown transcranial magnetic stimulation's significant potential in stroke research and treatment. Objective: This paper reviewed the research conducted on the utilization of transcranial magnetic stimulation in stroke from 1994 to 2023. This study applied bibliometric analysis to delineate the current research landscape and anticipate future research hotspots. Method: The study utilized the Web of Science Core Collection to retrieve and acquire literature data. Various software tools, including VOSviewer (version 1.6.19), CiteSpace (version 6.3.R1), Scimago Graphica (version 1.0.36), and WPS (version 11572), were used for data analysis and visualization. The review covered analyses of countries, institutions, authors, journals, papers, and keywords. Result: A total of 3425 papers were gathered. Top 3 countries were the United States (953 papers), China (546 papers), and Germany (424 papers) in terms of publication. The United States had the most cited counts (56,764 citations), followed by Germany (35,211 citations) and the United Kingdom (32,383 citations). The top 3 institutions based on the number of publications were Harvard University with 138 papers, the University of Auckland with 81 papers, and University College London with 80 papers. The most prolific authors were Abo, Masahiro with 54 papers, Fregni, Felipe with 53 papers, and Pascual-Leone, Alvaro with 50 papers. The top 3 journals in terms of papers collection were Neurorehabilitation and Neural Repair with 139 papers, Clinical Neurophysiology with 128 papers, and Frontiers in Neurology with 110 papers. The most frequently occurring keywords were stroke (1275 times), transcranial magnetic stimulation (1119 times), and rehabilitation (420 times). Conclusion: The application of TMS in stroke research is gaining momentum, with the USA leading in publications. Notable institutions such as Harvard University and University College London show potential for collaborative research. Key areas of focus include post-stroke cognitive impairment aphasia and dysphagia, which are expected to remain hotspots of future research. Future research should involve large-scale, randomized, and controlled trials in these fields. Identifying more effective combined therapies with rTMS is a priority.